HUBUNGAN ANTARA TINGKAT PENGETAHUAN TENAGA KESEHATAN TENTANG PENYEBARAN INFEKSI DENGAN KEPATUHAN MENCUCI TANGAN (FIVE MOMENT) DI RSD MANGUSADA - Susila, I Made Dwie Pradnya; Sumawati, Ni Made Risna (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Infections that occur in hospitals called Healthcare Associated Infections (HAIs) are a serious problem for public health. HAIs are infections that patients get during undergoing treatment procedures and medical procedures in health services after jam 48 hours and after ? 30 days after leaving the health facility. One way to reduce nosocomial infections is by washing hands. The purpose of this study was to determine the relationship between the level of knowledge of health workers about the spread of infection with five moment compliance. The design of this research is descriptive correlational research with the approach used is cross sectional approach. Determination of the sample in this study was chosen by the total sampling technique which amounted to 40 people. The data collection of knowledge about the spread of disease using questionnaires and hand washing data five moments using the observation sheet. The statistical test used in this study was Rank Spearman. The results of this study are p value 0.104 <0.05 so that the hypothesis is rejected ie there is no relationship knowledge knowledge of infection spread with the compliance of health workers in hand washing (five moments). Based on the results of this study, it is recommended that the Badung Mangunsada General Hospital be used as a reference in compliance with five moments hand washing by health workers so as to prevent the spread of infection.